Aprendendo através de quadrinhos: uma proposta metodológica para o ensino de Biologia - Azevedo, Ana Katarina Nascimento de (2020)
The research emerged from the verification that the teaching of Biology, in some pedagogical situations, presents itself unrelated to the student's daily life, promoting inefficient learning. This is due to the fact that the contents are taught in a fragmented way, not associating concepts with processes, in most cases, the student ends up memorizing terms instead of understanding them. This scenario cannot remain as students need essential knowledge for the citizenship exercise. Accordingly, the research is based on the construction of knowledge with the use of Comic Books (HQ) built by the students themselves, with the following objectives: to evaluate whether the method of self-construction would allow students to know what is necessary for them to develop their own learning, raise awareness to study Biology creatively; encourage the habit of reading and motivate them to understand Biology. The study is based on qualitative, documentary and bibliographic research. Two questionnaires were applied: one to assess previous knowledge and the other to know the content design and whether there was an incentive to read critically and creatively and the data analyzed through content analysis. It was developed at EE Jerônimo Gueiros (Natal / RN) with 32 students from 1st grade classes and took place from May to December 2019. The Comics production took place from the choice among the themes presented during the research groups period. They built 17 illustrations involving the themes of DNA or RNA molecule and ecology and 18 HQ with the themes: DNA and RNA, Replication and transcription, Photosynthesis, Respiration and Biomass. The scripts were carried out with the guidance of questions present in the Didactic Sequences answered by the students when investigating the contents. In the analysis of the questionnaires was verified that the reading habit was increased, that the students felt more motivated to study the subject, this motivation being triggered by the construction of the HQ. During the discussions while building the HQ, there was mutual collaboration, with reflection exercise and argumentation, especially related to what would be in the script. Finally, at the end of the activities there was an exhibition of Comics produced by students on a panel. As a product of this project, a guide was prepared presenting the experience and practice of using HQ in the teaching of Biology, which has the following title: “Guide to Didactic Sequences: a methodology that promotes the teaching-learning of Biology, through Comics” . It was concluded that, when working with HQ, students were sensitized to see Biology in a critical and creative way, being motivated to build their own learning. Finally, one can think that the use and creation of HQ favors learning and it can be used as an entertaining methodology in which the students themselves, when building their own ideas, through investigation and leadership, have their learning improvement.